Risk factors of postictal generalized EEG suppression in generalized convulsive seizures. (3rd November 2015) - Alexandre, Veriano; Mercedes, Blanca; Valton, Luc; Maillard, Louis; Bartolomei, Fabrice; Szurhaj, William; Hirsch, Edouard; Marchal, Cécile; Chassoux, Francine; Petit, Jérôme; Crespel, Arielle; Nica, Anca; et al.
Abstract : Objective: To identify the clinical determinants of occurrence of postictal generalized EEG suppression (PGES) after generalized convulsive seizures (GCS). Methods: We reviewed the video-EEG recordings of 417 patients included in the REPO2 MSE study, a multicenter prospective cohort study of patients with drug-resistant focal epilepsy. According to ictal semiology, we classified GCS into 3 types: tonic-clonic GCS with bilateral and symmetric tonic arm extension (type 1), clonic GCS without tonic arm extension or flexion (type 2), and GCS with unilateral or asymmetric tonic arm extension or flexion (type 3). Association between PGES and person-specific or seizure-specific variables was analyzed after correction for individual effects and the varying number of seizures. Results: A total of 99 GCS in 69 patients were included. Occurrence of PGES was independently associated with GCS type ( p < 0.001) and lack of early administration of oxygen ( p < 0.001). Odds ratio (OR) for GCS type 1 in comparison with GCS type 2 was 66.0 (95% confidence interval [CI 5.4–801.6]). In GCS type 1, risk of PGES was significantly increased when the seizure occurred during sleep (OR 5.0, 95% CI 1.2–20.9) and when oxygen was not administered early (OR 13.4, 95% CI 3.2–55.9). Conclusion: The risk of PGES dramatically varied as a function of GCS semiologic characteristics. Whatever the type of GCS, occurrence of PGES was prevented by early administration of oxygen.